2016
DOI: 10.1088/1742-6596/668/1/012076
|View full text |Cite
|
Sign up to set email alerts
|

The cool potential of gluons

Abstract: We put forward the idea that the quark-gluon plasma might exist way below the usual confinement temperature Tc. Our argument rests on the possibility that the plasma produced in heavy-ion collisions could reach a transient quasi-equilibrium with 'over-occupied' gluon density, as advocated by Blaizot et al. Taking further into account that gluons acquire an effective mass by interaction effects, they can have a positive chemical potential and therefore behave similarly to non-relativistic bosons. Relevant prope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…related to isospin, strangeness, electric charge etc., complicates the picture. Transient states related to under saturated or over saturated gluons [75] or under saturated quark state occupation [76] give rise to many interesting phenomena beyond our discussion.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…related to isospin, strangeness, electric charge etc., complicates the picture. Transient states related to under saturated or over saturated gluons [75] or under saturated quark state occupation [76] give rise to many interesting phenomena beyond our discussion.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…Particularly, expressions (96) do not contain terms ∝ 1/δn G . Nevertheless, if we substitute expressions (96) in the definitions (38) and (41), we obtain…”
Section: B Variances and Cross-variances Of The Particle Numbermentioning
confidence: 99%
“…The BEC can also occur because of an additional injection of non-equilibrium pions from resonance decays [35], decomposition of a blurred phase of hot baryon-poor and pion enriched matter existing before the chemical freezeout [36], sudden hadronization of supercooled quarkgluon plasma [37], and a decay of the transient Bose-Einstein condensate of gluons or glueballs pre-formed at an initial stage in a heavy-ion collision, cf. [38][39][40][41][42]. Reference [34] demonstrated that before the formation of the Bose-Einstein condensate the initially non-equilibrium interacting pion gas in ultrarelativistic heavy-ion collisions should pass several stages including a wave-turbulence stage.…”
Section: Introductionmentioning
confidence: 99%
“…Non-equilibrium supercooling effects [10][11][12], decays of resonances [13], or a decay of the transient BEC of gluons or glueballs pre-formed at an initial stage in a heavy-ion collision, cf. [14][15][16][17][18] may provide effective mechanisms to drive the pion system to the Bose-Einstein condensation (BEC). Reference [10] studied a possibility of the pion BEC in the interacting relativistic pion gas with a λϕ 4 interaction under the assumption that the number of pions created in the course of ultrarelativistic heavy-ion collisions is (dynamically) fixed in the time interval between the chemical and thermal freeze-outs.…”
Section: Introductionmentioning
confidence: 99%